Africa Alive Corridors: Transdisciplinary Research based on African Footprints - B. Linol; M. Doucouré; J. Anderson; F. Toteu; W. Miller; P. Vale; P. Hoffman; G. I. H. Kerley; R. Auerbach; C. Thiart; M. Meghraoui; N. Dhliwayo; et al. (Geoheritage, 2024)
The idea of Africa Alive Corridors (AAC) evolved from Gondwana geological mapping to a comprehensive, more inclusive and dynamic approach to transdisciplinary research known as Earth Stewardship Science. Twenty designated corridors explore the geo-biological and cultural heritage of different regions of Africa over various periods, from deep time to the Anthropocene. Each corridor reveals a specific lens through which to investigate some of the rich scientific narratives embedded within it. The concept also facilitates learning and knowledge exchange across numerous disciplines: archeology, geology, geophysics, oceanography, glaciology, biology, botany, ecology, agriculture, engineering, spatial statistics, social sciences, and the humanities. This contribution analyses ten selected corridors in southern and western Africa, the Congo Basin, East Africa, and Madagascar. The various research themes explored include Earth impact hazard, origins of humankind, Snowball Earth, coastal food systems and conservation, the biogeography of lemurs, human settlement dynamics in Cameroon, tectonically linked earthquake occurrences in Algeria and Morocco, modelling land-use changes in the Western Rift Valley, trades and civilizations of the Mali Empire, Mbira music, and contemporary art. The ongoing work on these—and ten other—corridors has considerable potential to host new international collaborations to develop the links between society and natural sciences in Africa. Ultimately, AAC will benefit all stakeholders, especially the youth, in understanding and responding to societal needs and current global challenges.

Forecast of precipitation for the 1994 flood in Piedmont: performance of an ensemble system at convection-permitting resolution - I. M. L. Cerenzia; G. Pincini; T. Paccagnella; E. Minguzzi; T. Gastaldo; V. Poli; M. S. Tesini; P. Patruno; D. Cesari (Bulletin of Atmospheric Science and Technology, 2020)
The major flood that affected the Piedmont region in Italy in November 1994 is re-forecast after 25 years in ensemble mode at the convection-permitting resolution of 2.2 km using the regional model COSMO. The performance of the probabilistic forecast of precipitation is assessed against rain-gauge observations, also in comparison with the driver system, i.e., the probabilistic re-forecast produced by ECMWF based on the operational IFS (Cycle 46r1) at grid spacings of 18 km. The convection-allowing system dynamically downscales the ECMWF ensemble and includes an explicit treatment of deep convection. Results indicate that both systems can predict up to 4 days in advance the timing and the spatial patterns of the precipitation, although with higher confidence for the convection-resolving system. The benefit of high resolution is shown mainly in the prediction of intense precipitation and in terms of correct amounts and locations, and confidence of occurrence (at day 3, the estimated probability of exceedance of 200 mm was higher than 90% over areas actually hit by such rainfall amounts). Additionally, convection-permitting resolution improves the representation of orographic precipitation, reducing the upwind precipitation displacement typical of coarser models and including the possible development of strong convection episodes embedded in the large-scale-forced orographic rise. For the high-resolution ensemble, the spread indicates large uncertainty at the local scale, mainly in defining the flow tendency to flank or flow over each mountain.

Cell death in human articular chondrocyte: a morpho-functional study in micromass model - M. Battistelli; S. Salucci; E. Olivotto; A. Facchini; M. Minguzzi; S. Guidotti; S. Pagani; F. Flamigni; R. M. Borzì; A. Facchini; E. Falcieri (Apoptosis, 2014)

PM10 Chemical Model Simulations Over Northern Italy in the Framework of the CityDelta Exercise - E. Angelino; M. Bedogni; C. Carnevale; G. Finzi; E. Minguzzi; E. Peroni; C. Pertot; G. Pirovano; M. Volta (Environmental Modeling & Assessment, 2008)